An Analysis of Students’ Anxiety in Learning English Speaking at SMAN 1 Masbagik - Susandi, Selis; Masyuroh, Siti; Prasetyaningrum, Ari; Yusri, Ahmad (IKIP Siliwangi, 2026)
This study aims to explore the factors contributing to students' anxiety when speaking English in the tenth grade at SMAN 1 Masbagik during the 2025-2026 academic year. A qualitative descriptive design was used, employing observation, interviews, and questionnaires as the main data collection instruments. The findings reveal that students experience three types of anxiety: communication concerns, test anxiety, and fear of negative evaluation. The main factors that trigger speaking anxiety include limited vocabulary, fear of making mistakes, pronunciation difficulties, and fear of negative evaluation. To overcome these challenges, students applied several strategies such as repeated practice, relaxation techniques, positive self-talk, preparing for language comprehension/grammar, and seeking peer support. This study concluded that student speaking anxiety is a multidimensional problem influenced by linguistic and psychological factors, requiring efforts from teachers and students to foster a more supportive learning environment.